PP31 Factors affecting variation in the uptake of HPV vaccine in secondary schools in the West Midlands. (2nd September 2014) - Chivu, CM; Clarke, A; Hundt, G
Abstract : Background: In 2008, the health departments of the United Kingdom implemented routine and catch-up human papillomavirus (HPV) immunisation programme in schools to reduce the incidence of cervical cancer. European studies conducted from 2007 to 2012 showed inconsistent results on HPV vaccine uptake in relation to ethnicity and girls' age. The aim of the study was to explore the views and experiences of students, teachers and health providers on the HPV vaccine to understand how mechanisms of delivery contributed to HPV vaccine uptake in a town in the West Midlands. Methods: Data was collected through 47 semi-structured individual interviews with nine nurses, four school staff and 34 year 8 girls as well as through non-participant observations in 12 schools during the delivery of the first, the second and the third dose of HPV vaccine between February and September 2013. The school staff and the girls were sampled from four secondary schools that accepted to participate in the study. Thematic analysis was employed to identify major themes related to the school context of implementation of the HPV vaccine programme in secondary schools in the town of the study. Results: Year 8 girls were aged 12–13 years. Some were Christian, Muslim and Hindu while others had no religion. The health professionals were nurse coordinators, school nurses, vaccinators, sexual health nurses and practice nurses. The school staff were teachers, support staff and head of year 8. Three main themes emerged from the analysis (1) school policy related to HPV vaccine, (2) the organisation of delivery of HPV vaccination programme in the schools before and on the day of vaccination, (3) promotion of HPV vaccine in schools. The findings showed that most of the schools have supported the delivery of the programme, but it has been more difficult for nurses to go to some of the faith schools in comparison to others. Chasing up the consent forms and communication with the parents have been the most challenging activities in the HPV vaccination administration, however they are essential for a high HPV vaccine uptake. The HPV vaccine was poorly promoted in the school environment because of tight curriculum for compulsory subjects and lack of adequate staff. Conclusion: Implementation of a school-based HPV programme is resource intensive in terms of time as well as of school staff and staff nurse.